Analisis Pengaruh Diskon, Promosi, Dan Kepercayaan Konsumen Pada Keputusan Pembelian Di Shopee - Larasati, Feby Ayu; Ronny, Ronny (Universitas Islam Kadiri, 2024)
This research aims to analyze and identify the influence of discounts, promotions and consumer trust on purchasing decisions. Research was conducted on consumers or customers who have made purchases at Shopee in the last few months with a total population of 105 people. The sample used was only 100 respondents because some samples did not match the criteria. Data collection techniques used were questionnaires via Google forms and conventional ones directly. Variable measurement uses a Likert scale with a scale of 1-7 and analysis for data processing uses the multiple linear regression method with the SPSS ver. 25. The research results show that discounts, promotions and consumer trust have a significant influence on purchasing decisions.